2005
DOI: 10.1021/jf0514524
|View full text |Cite
|
Sign up to set email alerts
|

Sensory and Foaming Properties of Sparkling Cider

Abstract: The effect of yeast strain and aging time on the chemical composition, analytical, and sensory foam properties of sparkling ciders has been studied. The analytical foam parameters (foamability, HM; Bikerman coefficient, sigma; and foam stability time, T(s)) were significantly influenced by aging and yeast strain. The sensory attributes (initial foam, foam area persistence, bubble size, foam collar, and overall foam quality) improved with aging time. Likewise, the yeast strain positively influenced the assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Nevertheless, it is not possible to generalize directly these results to real ciders. Indeed, concentration of CO 2 and the foam and bubble properties can vary in cider from one product to another depending on the fermentation process and cider composition (Blanco-Gomis, Mangas-Alonso, Exp osito-Cimadevilla, & Guti errezAlvarez, 2010; Gallart, Tom as, Suberbiola, L opez-Tamames, & Buxaderas, 2004;Picinelli Lobo et al, 2005;Rib ereau-Gayon, Dubourdieu, Dom eche, & Lonvaud, 2004). For this reason, further work will be needed to better understand the role of CO 2 in cider perception taking into account different levels of carbonation, the origin of the CO 2 (gasification, secondary fermentation in the bottle, etc.)…”
Section: From Model Solutions To Cidersmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, it is not possible to generalize directly these results to real ciders. Indeed, concentration of CO 2 and the foam and bubble properties can vary in cider from one product to another depending on the fermentation process and cider composition (Blanco-Gomis, Mangas-Alonso, Exp osito-Cimadevilla, & Guti errezAlvarez, 2010; Gallart, Tom as, Suberbiola, L opez-Tamames, & Buxaderas, 2004;Picinelli Lobo et al, 2005;Rib ereau-Gayon, Dubourdieu, Dom eche, & Lonvaud, 2004). For this reason, further work will be needed to better understand the role of CO 2 in cider perception taking into account different levels of carbonation, the origin of the CO 2 (gasification, secondary fermentation in the bottle, etc.)…”
Section: From Model Solutions To Cidersmentioning
confidence: 99%
“…Nevertheless, these authors worked on model solutions without including the sparkling components of cider due to the presence of CO 2 . In cider, the studies concerning CO 2 relate to the visual properties of foam and bubbles (Picinelli Lobo, Tasc on, Madrera, & Valles, 2005;Su arez Valles, Pando Bedriñana, Lastra Queipo, & Mangas Alonso, 2008). None mentions the interaction between CO 2 and cider chemical components although there is much evidence indicating that carbon dioxide could modulate taste and astringency in different matrices (Saint-Eve et al, 2009.…”
Section: Introductionmentioning
confidence: 99%
“…Good foaming behavior in ''natural" cider includes the initial formation of a large amount of foam when it is poured in the glass, followed by its rapid disappearance forming little bubbles of carbonic gas; finally a rest of thin foam should stay in the glass. The typical visual attributes assessed in sparkling cider are initial foam, foam area persistence, number of nucleation sites, bubble size, and foam collar (Picinelli Lobo, Fernández Tascón, Rodríguez Madrera, & Suárez Valles, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The typical visual attributes assessed in sparkling ciders are: initial foam, foam area persistence, number of nucleation sites, bubble size and foam collar (Picinelli Lobo, Fernández Tascón, Rodríguez Madrera, & Suárez Valles, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Picinelli Lobo et al (2005) demonstrated the influence of ageing time and yeast strain on the foaming properties of sparkling ciders. The yeast strain significantly influenced foamability and Bikerman's coefficient (Bikerman, 1938), while ageing time significantly influenced foamability and foam stability time.…”
Section: Introductionmentioning
confidence: 99%